ANALISIS RASIO KEUANGAN TERHADAP RETURN SAHAM DAN NILAI PERUSAHAAN - Chotimah, Chusnul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out the analysis of financial ratio to the companyâs stock and value (TobinsâQ). Samples in this research are metal and chemical industry manufacturing companies which are listed in the Indonesia Stock Exchange during the period of 2008â2012 periods by using purposive sampling method. The statistic test method is using the multiple linear regressions analysis in this research. Current Ratio, Total Assets Turn Over, Debt to Equity Ratio, Return on Assets, Return on Equity, Price Earnings Ratio are used as independent variables in this research, stock return and companyâs value (TobinsâQ) are used as dependent variables. The result of research shows that current ratio has no significant influence to the stock return and TobinsâQ. Total Assets Turn Over has no significant influence to the stock return but it has significant influence to the TobinsâQ while Debt to Equity Ratio, Return on Assets, Return on Equity, Price Earnings Ratio have significant influence to the stock return and TobinsâQ.Keywords: Financial Ratio, Company Performance, Stock Return, and TobinsâQ.